An Observational Study on Premenstrual Symptoms and Dysmenorrhea Among Nursing Students - Ashoka, Ankita; Kollur, Lata Radhakrishna (National Journal of Community Medicine, 2015)
Background: The distressing symptoms of Premenstrual syndrome have been recognized for centuries by physicians. Material and methods: An Observational study including a total of 79 First year BSc Nursing students of SDM College of Nursing Sciences was carried out over a period of 3 months.Predesigned se- mistructured questionnaire containing questions regarding sociode- mographic profile,menstrual cycle abnormalities, dietary habits and physical exercise was used for data collection. Premenstrual Symp- tom reporting diaries were given to participants for reporting symp- toms over a duration of two consecutive menstrual cycles. Results: Total 79 girls studying in first year BSc nursing were in- cluded in the study. Mean age of participants was 17.8 years. Mean age at attainment of menarche was 13.4 years. Out of 79 girls 6(7.59%) had irregular menses. Heavy flow during menses was noted by 18 participants. Dysmenorrhoea was reported by 58(73.4%) participants. One or more symptoms during the two consecutive menstrual cycles were reported by 29 (36.7%) participants. No statistically significant association was found between occurrence of Premenstrual symp- toms and consumption of junk food, exercise, consumption of sugar, salt and citrus fruits. Conclusion: Even though menstruation is a physiological process, many suffer from disorders of menstruation and premenstrual symp- toms, which needs attention.